Narrative of a tour through Armenia, Kurdistan, Persia and Mesopotamia, with an introduction and occasional observations upon the condition of Mohammedanism and christianity in those countries. - Southgate, Horatio, 1812-1894 ([Boston])
2 c. (xii, 334 s. ; x, 356 s.)